Uncertainty in illness and coping styles: Moderating and mediating effects of resilience in stroke patients - Zi Ting Han (2022)
BACKGROUND Stroke has a great influence on the patient's mental health, and reasonable psychological adjustment and disease perception can promote the recovery of mental health. AIM To explore the relationships among resilience, coping style, and uncertainty in illness of stroke patients. METHODS A retrospective study was used to investigate 154 stroke patients who were diagnosed and treated at eight medical institutes in Henan province, China from October to December 2019. We used the Mishel Uncertainty in Illness Scale, the Connor-Davidson Resilience Scale, and the Medical Coping Modes Questionnaire to test the uncertainty in illness, resilience, and coping style, respectively. RESULTS Resilience had a significant moderating role in the correlation between coping style and unpredictability and information deficiency for uncertainty in illness (P < 0.05). Further, the tenacity and strength dimensions of resilience mediated the correlation between the confrontation coping style and complexity, respectively (P < 0.05). The strength dimension of resilience mediated the correlation between an avoidance coping style and the unpredictability of uncertainty in illness (P < 0.05), as well as correlated with resignation, complexity, and unpredictability (P < 0.05). CONCLUSION Resilience has moderating and mediating roles in the associations between coping style and uncertainty in illness, indicating that it is vital to improve resilience and consider positive coping styles for stroke patients in the prevention and control of uncertainty in illness.